Prognozowanie preferencji nabywców nieruchomości mieszkaniowych - Bartłomowicz, Tomasz (Forecasting of Preferences of Properties' Purchasers, 2006)
The paper presents the application of the poll opinion method in forecasting of preferences of potential properties' purchasers, placed in the Jelenia Gora area, intended in the local spatial development plan for new' housing. The source was some results of questionnaire research organized by the author among potential properties' purchasers in June, July and August 2005. In the article there are the answers of the questions about such problems as: what is the most wanted and unwanted location of properties, area and environment (surroundings), what features which characterize the properties will be highly valued, what will be the aim of properties' purchasing, in what kind of building should be a new flat. In author's opinion the prognosis of preferences of properties' purchasers are detached to developers and other investors from real estate market.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1112, s. 160-167